IMPLEMENTASI KEBIJAKAN PROGRAM DAPUR SEHAT ATASI STUNTING DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Shafa Laksmi Aziza; Garmana, Deden Haria; Hendryawan, Shofwan (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to determine the Implementation of the Healthy Kitchen Program Policy to Overcome Stunting in Cimalaka District, Sumedang Regency. The method used is a qualitative method with a descriptive type. Data collection techniques were carried out through literature studies and field studies which included: observation, interviews, documentation and triangulation. The final results of this study conclude that the Implementation of the Healthy Kitchen Program Policy to Overcome Stunting in Cimalaka District, Sumedang Regency has been running well and provides significant benefits to the community, the government and stakeholders have responded positively to this program, but not yet fully maximized. This is indicated by the following findings: (1) lack of socialization to the community which should be carried out in each sub-district in each village (2) lack of resources, the budget for the program can be implemented optimally. The efforts made are to carry out comprehensive outreach to implementers and the community. The policy implementation of the Healthy Kitchen Program to Overcome Stunting in Cimalaka District has been running by involving various parties, including the local government, posyandu cadres, and the community. This program focuses on providing balanced nutrition education, managing healthy kitchens, and providing additional food for children at risk of stunting. Based on the results of the study, there are several suggestions, namely for this study, namely that it can increase socialization activities on a regular basis to help provide understanding to the target of socialization about the purpose and objectives of this atasi stunting program.